Unlocking Potential: Strategies for Recruiting and Supporting Veterans on the Path to Success in College - Latosha R. Henderson; Kurtis D. Watkins (Journal of Postsecondary Student Success)
Higher education in the United States is currently grappling with two significant challenges that threaten its sustainability: the repercussions of the COVID-19 pandemic, which has led to a decline in enrollments, and the 2023 Supreme Court decision to prohibit affirmative action in college admissions. This essay explores how these challenges affect student success and diversity, equity, and inclusion principles, emphasizing the urgent need for innovative recruitment of underrepresented student groups. Veterans, specifically those with some college credit but no credential (VSCNC), represent a promising yet overlooked demographic within traditional recruitment strategies. According to the National Student Clearinghouse, over 40 million adults in the United States belong to the “some college, no credential” group. Notably, 76% of post-9/11 veterans have some college credit but lack a bachelor’s degree (Hill et al., 2019). This essay emphasizes the necessity of developing tailored strategies to support VSCNC, a group that has been historically underrepresented in higher education despite their significant educational resources, skills, and abilities to perform well and succeed in college. By addressing barriers and leveraging veterans’ diverse perspectives, institutions can improve recruitment and academic success, fostering a more inclusive and equitable educational environment.